Clinical and Epidemiological Features of COVID-19 in Children in Moscow in 2020–2022 - E. R. Samitova (Эпидемиология и вакцинопрофилактика)
Relevance. COVID-19 pandemic predetermines the relevance of the analysis of clinical and epidemiological peculiarities in different periods of morbidity growth in the pediatric population.Aim. To identify clinical and epidemiological features of the course of COVID19 in Moscow among children (2020–2022).Materials and Methods. The retrospective clinical and epidemiological analysis of the incidence of COVID-19 among children in Moscow over a two-year period (March 9, 2020 to March 30, 2022) was performed. We used data from case histories of 3092 children diagnosed with U07.1, hospitalized in infectious diseases departments for children with COVID-19 at Bashlyaeva Children's Clinical Hospital of Moscow and materials from Rospotrebnadzor report No 970 «Information about cases of infectious diseases in persons with suspected new coronavirus infection», information portal Stopcoronavirus.rf and others. The presence of SARS-CoV-2 RNA was confirmed by real-time reverse transcription polymerase chain reaction.Results. Five upsurges of morbidity differing by clinical and epidemiological manifestations of the course of COVID-19 were distinguished. In the first period of morbidity rise (March–June, 2020) the age groups 7–14 and 14–17 years prevailed, in the fifth period (January 2022–March 2022) infants and young children prevailed. The most frequent severe and critical forms of COVID-19 were registered in the genovariate delta due to lung lesions, less frequently in the omicron strain. Comorbid pathology in children during all periods of the pandemic was a risk factor for severe course and unfavorable outcome of the disease. In general, the number of children hospitalized in intensive care unit (ICU) decreased: 3.7%. 4,7%, 4,7%, 3,3%, 3,2%. Administration of viral neutralizing monoclonal antibodies to SARS-CoV-2 to children at risk for severe disease during the fourth and fifth waves of COVID-19 reduced the number of children hospitalized in the ICU, despite the high morbidity rise than in the previous waves of COVID-19.Conclusion. Each of the five identified COVID-19 morbidity bursts among children had its own features. The proportion of severe infection among hospitalized children was 3.7%, 4.7%, 4.7%, 4.7%, 3.3%, 3.3% according to the waves of morbidity rise. During the first two waves of COVID-19, the disease occurred as acute respiratory infections (80%). In the second wave, the proportion of children hospitalized in the ICU with a multisystem inflammatory syndrome reached 57.6%. In the third wave of COVID-19 there was an increase in the number of cases of bilateral viral pneumonia (34.8%), severe forms of pneumonia (CT-3-4) in children with comorbid diseases. In the fourth period the structure of hospitalized children in the ORIT was 72.3% of children from the risk group. During the fifth wave of COVID19, the number of infants and young children hospitalized increased (49%) in the early period of admission from the onset of the disease (44%).